Pelatihan Future Career Planning untuk Meningkatkan Future Orientation Santri - Metha Irmawayani Putri; Zulmi Ramdani; Yonathan Natanael; Feri Indra Irawan (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
This study aims to examine the effectiveness of future career planning training on improving the future orientation of students at one of the Islamic boarding schools in Tasikmalaya. The research design used a quasi experimental study using a mixed-method design involving 25 students who were selected through quota sampling. Training is given for 5-6 hours on the same day, wherein the training program and modules were developed by the researcher. The result of this study using stacking analysis showed that 13 participants experiencing an increase in future orientation while testing with paired t-test for all participants didn’t show a significant difference in the logit value means from before and after being given training. Future career planning training that developed is quite feasible to be used regularly to see the consistency of students’ future orientation.